The application of stapedoplasty for the treatment of hearing loss in the patients suffering from obliterative otosclerosis - Kryukov, A I; Garov, E V; Zelikovich, E I; Sidorina, N G; Fedorova, O V; Zelenkova, V N; Kaloshina, A S; Zagorskaya, E E; Kurilenkov, G V; Kiselyus, V E (Vestnik otorinolaringologii, 2017)
This article presents the results of analysis of the data obtained during the examination and the surgical treatment of the patients presenting with the obliterative form of otosclerosis and suffering from hearing impairment with special reference to the intraoperative findings, technical aspects of stapedoplasty, and its effectiveness. A total of 14 patients (17 ears) were recruited for the participation in the present study including 10 women at the mean age of 38.8±6.2 years and 4 men (mean age 44.8±3.9 years). The duration of the hearing loss in the period preceding the surgical treatment in 7 (50%) patients was more than 8 years. According to the results of tonal threshold audiometry (TTA), the mean bone conduction (BC) threshold for conductive hearing loss in the frequency range from 0.5 to 4.0 kHz was 24.9±8.1 dB with the mean bone air gap (BAG) equaling 38±5.1 dB. Computed tomography (CT) of the temporal bones revealed grade 1 obliterative otosclerosis in 4 patients, grade II of the same condition in 6 patients, and grade III in 7 ones. These findings were confirmed intraoperatively. In 15 cases, stapedostomy was carried out with the use of the non-contact CO2 laser-based system, in the remaining cases a microdrill was employed. Five patients underwent laser-assisted piston stapedoplasty while in 11 others the stapes prosthesis was placed on the autovein. One patient was treated by the same method with the use of the autocartilaginous prosthesis. The functionally acceptable results within 1 year after the surgical intervention were obtained in all the treated patients with the mean bone air gap equaling 13.2±3.4 dB. The best outcome (the reduction of the BC threshold and BAG by 7 dB and 25.9 db on the average respectively within 1 year after surgery was achieved in the patients with grade III obliterative otosclerosis.